BEBERAPAASPEK BIOLOGIIKAN PETEK, Leiognathus splendens CUVIER DIPERAIRAN TELUK LABUAN, B ANTEN [Some biological aspects of splendid ponyfish Leiognathus splendens Cuvier in Labuan Bay, Banten] - Djadja S. Sjafei; Saadah Saadah (Jurnal Iktiologi Indonesia, 2001)
The research was conducted in Labuan bay of Banten Province from Avril - June 1999. The numbers offish collected were 747 (539 male and 208 female). The lengths ot male were 49- 145 m with 1.69-51.36 grams in weight, while the female had ranged 49- 161 mm in length and 1.84 - 57.88 gram in weight. The length of the male was primarily in size 73 - 84 mm, the female in 121 - 132 mm. Based on length weight relationship the fish was isometric. Condition factor of the male ranged 0.447 - 2.752, and 0.589 - 2.285 of the female The stomach dominated by undetermined materials. The fish food was dominated by Baccilariophyceae (15 genera the most was Synedra). The secondary group were Pleurosigma, Nitssliia, and ThaUasiotrix. Other foods were Desmidiaceae, Chlorophyceae, Dynophyceae. Copepoda, Ciliata and Sarcodina. Maturity stage of the male ranged between I - IV (dominated by stage I). Maturity stage of the female were ranged between I - V and dominated by stage IV. The gonado somatic index of male ranged between 0.45 - 2.13, while of female between 0.35 - 2.45.ABSTRAKPenelitian dilaksanakan di Teluk Labuan, Banten dari bulan April - Juni 1999. jumlah ikan yang dikoleksi 747 ekor (539 jantan dan 2008 betina). Ukuran panjang ikan antara 49 - 145 mm, dengan berat antara 1,69 - 51, 6 gram. Ikan betina berkisar antara 49-161 mm dan berat 1,84 - 57,88 gram. Ikan jantan terutama banyak pada ukuran 73 - 84 mm. betina pada 121 - 132 mm. Berdasarkan huhungan panjang berat pertumbuhan ikan bersifat isometnk. Faktor kondisi jantan 0,497 - 2,752; betina 0,589 - 2,285. Isi perut didominasi oleh materi yang tidak teridentifikasi. Makanan didominasi oleh Baccilariophyceae (15 genera tterutama Synedra), yang berikutnya Pleurosigma, Nitschia, dan ThaUasiotrix. Yang Iain adalah Desmidiaceae, Chlorophyceae, Dynophyceae, Copepoda, Ciliata, dan Sarcodina. Tingkat kematangan gonad jantan berkisar I - IV (didominasi oleh stadia I). Tingkat kematangan gonad betina berkisar antara I — V yang didominasi oleh stadia IV, Indeks kematangan gonad pada jantan berkisar 0,45 - 2,13; pada betina antara.0,35 - 2,45.